ANALISIS REGULASI HIGIENE INDUSTRI LINGKUNGAN KERJA PT PERTAMINA PATRA NIAGA - SOEKARNO HATTA FUEL TERMINAL AND HYDRANT INSTALLATION - Rosika Hartanto, Aldyan; Pradnyana Putra, I Dewa Gede Deva; Dian Arfiani, Novi (Dian Nuswantoro Semarang, 2024)
To ensure the safety and efficiency of an industry, it is crucial to monitor various fundamental factors such as lighting, temperature, humidity, and noise in accordance with regulations established by the Minister of Health. This study assesses the physical conditions, covering these factors, within the work environment at PT Pertamina Patra Niaga Soekarno Hatta Fuel Terminal and Hydrant Installation. The research methodology includes a compliance evaluation based on monitoring reports spanning from January to July 2023, comparing the results with relevant regulations. The findings reveal adherence to lighting and noise standards, although 5 rooms fall short of the temperature criteria, and 4 rooms do not meet the humidity requirements. The effective implementation of industrial hygiene standards in the workplace is imperative for ensuring the safety of workers and the preservation of the environment.